2015
DOI: 10.1590/0103-644020130087
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silver Nanoparticles Reduces Internal Contamination of External Hexagon Implants by Candida albicans

Abstract: Since the dental implant/abutment interface cannot totally seal the passage of microorganisms, the interior of implant becomes a reservoir of pathogenic microorganisms that produce and maintain chronic inflammation in the tissues around implants. Silver nanoparticles (nano-Ag) are potent and broad-spectrum antimicrobial agents. The aim of this study was to evaluate the capacity of the nano-Ag to prevent the contamination of the implant internal surface by Candida albicans, caused by the implant/abutment microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…are key colonizers, and play a major role in the formation of catheter lumen and other implant biofilms, the reduction or inhibition of Candida colonization on the surface of these medical devices, is a key to prevent recalcitrant infections (see above) [176]. We discuss below the major candidate vaccines currently being explored, namely fungal cell-wall .…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…are key colonizers, and play a major role in the formation of catheter lumen and other implant biofilms, the reduction or inhibition of Candida colonization on the surface of these medical devices, is a key to prevent recalcitrant infections (see above) [176]. We discuss below the major candidate vaccines currently being explored, namely fungal cell-wall .…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Bacterial adhesion to the surface of implants may result in peri-implant diseases and cannot always be avoided by sterilization before implantation. AgNPs coating produced a strong antibacterial effect on the titanium surface by inhibiting the adhesion of bacteria (Massa et al, 2014;Matsubara et al, 2015;Mishra et al, 2015;Qin et al, 2015;Vogel et al, 2015). In our study, AgNPs were incorporated to the surface of dental alloys to improve their antibacterial properties, in order to further reduce the incidence of denture stomatitis and peri-implantitis.…”
Section: Discussionmentioning
confidence: 87%
“…Microwave solidification was applied to the denture base preparation after mixing the AgNPs with polymethyl methacrylate (PMMA) powder, and the results showed that the amount of C. albicans attached to the base surface was significantly reduced (Acosta-Torres et al, 2012). AgNPs have also been added to the surface of titanium implants (Massa et al, 2014;Matsubara et al, 2015;Mishra et al, 2015). This incorporation of AgNPs not only resulted in a significant increase in antibacterial properties (Streptococcus mutans (MS), Porphyromonas gingivalis, and C. albicans), but also significantly increased the expression of osteoblast phenotype genes (Alp, Ocn, RunX2) in cell growth on the Ag-implanted titanium surface (Zheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing interest in the use of nanomaterials in medical devices to exert therapeutic effects, e.g., antimicrobial effects, blockage of inflammatory responses, inhibition of oxidative stress, reduction of cell proliferation, among others. [1][2][3] Layers of nanoparticles can be deposited on implantable devices (e.g., stents, pacing leads, balloons, vascular closing devices, etc. ), which can either be permanently bound to the device to exert local antimicrobial effects or designed to release a flux of appropriately-sized nanoparticles to a patient after implantation in the body.…”
Section: Introductionmentioning
confidence: 99%
“…2 Statistical analysis was performed to compare the body weights between Day-0 and Day-28, for all groups using paired T-test. This showed significant increase (#, P < 0.05; ##, P < 0.01; ###, P < 0.001) in body weights in all groups 3. Statistical analysis (unpaired T-test) was performed to compare the body weights between untreated/control group and CeO-NP implanted groups.…”
mentioning
confidence: 98%